1979
DOI: 10.1111/j.1398-9995.1979.tb01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Skin Tests and RAST for the Diagnosis of Bee Sting Allergy

Abstract: Skin tests and estimation of specific IgE-antibodies by the RAST are evaluated as diagnostic procedures in bee sting hypersensitivity with the followiny extracts. (2) With bee venom results of skin tests and RAST correspond in 82%, with bee wholebody extracts in 68%. (3) Both with skin tests and the RAST with bee venom a good discrimination between patients with bee sting hypersensitivity and non-allergic controls is observed. Skin tests with bee venom are somewhat more sensitive than bee venom-RAST. (4) With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 10 publications
1
15
0
1
Order By: Relevance
“…Six patients (5.3%) had a negative ICST but were sensitized to WV. Such differing results have also been observed by others (20,21). Patrizzi et al.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Six patients (5.3%) had a negative ICST but were sensitized to WV. Such differing results have also been observed by others (20,21). Patrizzi et al.…”
Section: Discussionsupporting
confidence: 66%
“…Patrizzi et al. (21) found that 24.3% of 33 BV hypersensitive patients had a positive ICST but no specific IgE. Only one patient had a negative skin test but specific IgE.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro tests used to detect allergen-specific IgE antibodies in the serum hardly ever identify all skin-test-positive subjects (14)(15)(16). The levels of specific IgE antibody may be too low, or high concentrations of allergen-specific IgG antibodies may interfere with IgE binding (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] It is generally accepted that a positive intradermal skin test response to insect venom at a concentration of less than or equal to 1.0 mg/mL demonstrates the presence of specific IgE antibodies. [19][20][21][22] Skin testing with fire ant whole-body extract is considered indicative of specific IgE antibodies if a positive response occurs at a concentration of 1:100 wt/vol or less by using the skin prick method or 1:1,000 wt/vol or less by using the intradermal method. 13,14,17 For those patients who have negative skin test responses despite a convincing history of anaphylaxis after an insect sting, especially if they experienced serious symptoms, such as upper airway obstruction or hypotension, it is advisable to consider in vitro testing for IgE antibodies or repeat skin testing before concluding that immunotherapy is not indicated.…”
Section: Executive Summarymentioning
confidence: 99%